Fatal Judgment : An Andy Hayes Mystery - Welsh-Huggins, Andrew (Book collections on Project MUSE., 2019)
"Judge Laura Porter fiercely guarded her privacy, and never more so than during her long-running--and long in the past--affair with disgraced quarterback-turned-private investigator Andy Hayes. Now she's missing, disappeared just hours after she calls Andy out of the blue explaining she's in trouble and needs his help. A trail of clues leads Andy to a central Ohio swamp whose future lies in the judge's hands as she weighs a lawsuit pitting environmentalists against developers. Soon Hayes encounters the case of another missing person, a young man who vanished without a trace in a different swamp two counties away. As he looks for links between the two disappearances, Hayes is led from Columbus to Cleveland, unearthing a history of secrets and betrayals threatening not just the judge but her family as well. Along the way, Hayes is forced to confront a newly strained relationship with his oldest son, now a budding football star himself, and revisit his tumultuous days as a Cleveland Browns quarterback and the gridiron failures that haunt him to this day. In partnership with a female cop on her own quest for justice, Hayes rushes to find the judge, and the truth, before it's too late"--